Analisis Status Nitrogen Tanah dalam Kaitannya dengan Serapan N oleh Tanaman Padi Sawah di Kelurahan Ujung Bandar, Kecamatan Rantau Selatan, Kabupaten Labuhan Batu - Dimas Ariansyah Putra; Dini Hariyati Adam; Novilda Elizabeth Mustamu; Fitra Syawal Harahap (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2022)
The presence of nitrogen in the soil is closely related to plant growth. The purpose of the study was to analyze the availability of nitrogen in the soil and calculate the need for fertilizers to increase the productivity of lowland rice. This research was carried out in rice fields in the village of Ujung Bandar, South Rantau distric, Labuhan Batu and analysis of soil samples in the laboratory on January 16, 2022.The study used a survey method with a sample area approach on a land area of ​​300 m2. The results showed that the N in paddy fields was low (UB 3, UB2 and UB1), starting from 0.11%, 0.14% and 0.15%. The addition of fertilizers with nitrogen content is needed to support plant growth in increasing productivity.